PHYSICOCHEMICAL PROPERTIES OF FLOUR AND STARCH OF PURPLE WATER YAM (Dioscorea alata) TUBER AND THE DIFFERENCE ON SENSORY ACCEPTANCE OF THE COOKIES PRODUCED - Risa Nofiani; Selvia Ulta; Dewi Safitri; Lia Destiarti (AGROINTEK, 2021)
Purple water yam tubers (PWYTs) or Dioscorea alata are edible tubers containing bioactive compounds that are beneficial to human health. Its high carbohydrate content can be used to make flour or starch to increase its shelf life and food diversification. However, this food is unpopular among several communities in Indonesia, particularly for the juveniles due to limited processing knowledge. Therefore, this study aims to characterize the physicochemical properties of purple water yam flour (PWYTF) and starch (PWYTS) in order to assess consumers' acceptability toward gluten-free cookies. The PWYTF was prepared by drying peeled tubers, which was subsequently grounded. Meanwhile, the PWYTS was prepared by homogenizing the peeled tubers with water, the sediment from supernatant was dried. The chemical properties, such as moisture, ash, fiber, protein, and lipid, were determined using the Indonesian national standard procedures for flour. The physical properties, namely pH, bulk density (BD), water/oil absorption capacity (W/OAC), water/oil binding capacity (W/OBC), swelling power (SP) and solubility (Sol) were evaluated. The PWYTF and the PWYTS were used to make gluten-free cookies, with their physical properties and consumer's acceptability evaluated using semi-trained panelists. Yields of both the PWYTF and the PWYTS were 36.10% and 26.63%, respectively. The chemical compositions of the PWYTF and the PWYTS were significantly different (p0.05) for carbohydrate (80.34 and 80.78 %), crude protein (0.78 and 0.81%), and crude fiber (2.0 and 1.9%) except for the ash content (2.6 and 0.5%), lipid (0.3 and 0.1%), and moisture (13.77 and 15.70%). Furthermore, their physical properties were also significantly different (p0.05) for pH (6.62 and 5.84), BD (0.46 and 0.68 g/mL), WAC (2.07 and 0.46 g/g), WBC (1.07 and 0.49 g/g), SP, and Sol except OAC (1.63 and 1.49 g/g) and OBC (0.63 and 0.49 g/g). The cookies made from the PWYTS were appreciated with the highest hardness and rated from panelists. Therefore, the PWYTS can be used in place of a commercial wheat flour to make cookies..